The CYP303A1 is essential in embryonic development of Nilaparvata lugens Stål (Hemiptera: delphacidae) - Liu, Yingzhen; Yan, Zihan; Deng, Di; Wang, Huaiqi; Mao, Ziyue; Tang, Enrui; Zhong, Junyi; Zhao, Xudong; Ge, Linquan (Frontiers in Physiology, 2025)
The N. lugens is a highly fecund rice pest that causes severe damage to rice production in Asia. Cytochrome P450 monooxygenases (P450s) play essential roles in insect development, metabolism, and reproduction. In a previous study, we identified and functionally characterized CYP303A1, a member of the CYP2 family, in N. lugens molting and metamorphosis process. However, it is unclear the function of CYP303A1 in N. lugens fecundity. In this study, the expression profiling showed that CYP303A1 is highly expressed in legs and adult fat bodies, with moderate expression in the ovaries. Silencing of CYP303A1 in females had no significant effects on Vg (Vitellogenin) and VgR (Vitellogenin receptor) transcript levels, ovarian morphology, oocyte number, oviposition period, or female lifespan, indicating that CYP303A1 is not involved in vitellogenesis or ovarian development. However, knockdown of CYP303A1 significantly prolonged the embryonic period and reduced egg hatchability. Morphological observations revealed that silencing CYP303A1 led to abnormal embryonic development, including delayed eyespot formation and dispersed yolk granules. Furthermore, the expression levels of several egg hatchability-related genes, including Cpr52, TwdIE3, HNF4, and Let1, were significantly altered following CYP303A1 silencing. These findings suggest that CYP303A1 is essential for successful embryogenesis in N. lugens, likely by regulating the expression of hatching-related genes. This work expands our understanding of the non-Halloween CYP genes in insect reproduction and provides a potential molecular target for disrupting N. lugens population development.